Peran religiusitas dan wisdom terhadap sikap menghadapi kematian bagi masyarakat Jawa pada masa pandemi covid-19 - Yuwono, Emmanuel Satyo (Jurnal Psikologi Udayana, 2021)
This study aims to reveal the role of wisdom and religiosity in the attitude of facing death in Javanese society during the Covid-19 pandemic. The research was conducted in Desa Banyubiru, Kab. Semarang, Central Java, with a total of 50 participants. This study applies three measurement scales, namely (1) the self-assessed wisdom scale (SAWS) developed by Webster (2003); (2) The Centrality of Religiosity Scale (CRS) developed by Huber & Huber (2012); and (3) Death Attitude Profile-Revised (DAP-R) developed by Wong, Reker, & Gesser (1994). The measurement scale has been modified into Indonesian language because of the environmental context of the research participants. This research draws upon quantitative approach with multiple regression statistical analysis. The results showed an F value of 5.743 with a level of significance 0.006 (p <0.05), which means religiosity and wisdom has simoultanesly impact towards the death attitude in Javanese society. The amount of contribution given by the two independent variables together is 19.6%. the further researchers require to consider the cultural, environmental, and socioeconomic context in referring attitudes toward death